Pengembangan Media Pembelajaran Dosean Pada Materi ASEAN - Ainun Fitri Yadi; Ima Rahmawati; Rusdiono (JURNAL KAJIAN ISLAM MODERN, 2023)
This research is motivated by a problem which is known that there are still students who are not active in class VI in Social Sciences (IPS) subjects on ASEAN material, because IPS is a subject that has a lot of memorization and in the ASEAN material there are many country names. , figures and years that make students have difficulty with material about ASEAN so that domino cards are needed to concretize the material in these subjects. The purpose of this research is to develop educational game-based learning media DOSEAN (Domino Asean) on the material contained in the thematic books of SD/MI grade 6 theme 1 "Save Living Things" sub-theme 1 "Plants my best friend" on pages 8 and 9 of the IPS topic about ASEAN at SDN Tegallangkap 01, Bogor Regency. Research and Development (R&D) is the approach used in this study with a research design that is able to produce products, so using research that is needs analysis in nature, with the ADDIE method, but only up to the Analysis, Design, and Development stage. The results of media validation were obtained with a percentage of 95.3% and material validation with a percentage of 96%. Then the research results from the validation are categorized as "Very Valid" and DOSEAN learning media is feasible to use